2016
DOI: 10.5713/ajas.15.0429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Levels of Fungal (<i>Arachniotus</i> sp.) Treated Wheat Straw as an Ingredient of Total Mixed Ration on Growth Performance and Nutrient Digestibility in Nili Ravi Buffalo Calves

Abstract: The study was carried out to explore the effects of replacing wheat straw with fungal treated wheat straw as an ingredient of total mixed ration (TMR) on the growth performance and nutrient digestibility in Nili Ravi buffalo male calves. Fungal treated wheat straw was prepared using Arachniotus sp. Four TMRs were formulated where wheat straw was replaced with 0 (TMR1), 33 (TMR2), 67 (TMR3), and 100% (TMR4) fungal treated wheat straw in TMR. All TMRs were iso-caloric and iso-nitrogenous. The experimental TMRs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The dry matter digestibility of fungal treated WS in our study was improved by 12% which was higher than that (7% and 10%) reported by Shahzad et al [10] and Fazaeli et al [26], respectively. Similar trend was observed in higher digestibility of crude protein, NDF, ADF and gross energy where the digestibility of these parameters were 27%, 28%, 2% and 12%, respectively (Table 2).…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…The dry matter digestibility of fungal treated WS in our study was improved by 12% which was higher than that (7% and 10%) reported by Shahzad et al [10] and Fazaeli et al [26], respectively. Similar trend was observed in higher digestibility of crude protein, NDF, ADF and gross energy where the digestibility of these parameters were 27%, 28%, 2% and 12%, respectively (Table 2).…”
Section: Resultscontrasting
confidence: 83%
“…Shahzad et al [10] showed that fungal treatment of WS increased CP and ash contents while cell wall contents were reduced. Similar effect of fugal treatment is on improving crude protein value in pea nut husk [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RCK-1 instead of untreated wheat straw, both of which were fed ad libitum and supplemented with a concentrate. Shahzad et al (2016) also reported greater DMI and digestibility when white-rot fungi-treated wheat straw was used to replace 33% of the untreated wheat straw in a TMR fed to buffalo calves.…”
Section: White-and Brown-rot Fungimentioning
confidence: 90%
“…These livestock species are resistant to endemic diseases, can survive in harsh environment and e ciently convert low quality forages into milk, meat and hide (Younas and Yaqoob, 2005). There is, however, a dire need of time to increase the production potential of the livestock to ful l the needs of rapidly growing population (Shahzad et al 2016).…”
Section: Introductionmentioning
confidence: 99%